2011
DOI: 10.1253/circj.cj-11-0780
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lipid Profile and Risk of Atrial Fibrillation - Niigata Preventive Medicine Study -

Abstract: Background: Dyslipidemia, an important risk factor for cardiovascular disease, may be associated with atrial fibrillation (AF). Cross-sectional studies that have examined this association, however, have produced controversial results, and few longitudinal studies have been conducted. Methods and Results:Using annual health examinations in Japan, the association between lipid profile and the risk of new-onset AF was investigated in the general population. A total of 28,449 individuals who did not have AF at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 44 publications
10
100
1
6
Order By: Relevance
“…A longitudinal study of the results of health examinations in Japan revealed an inverse association between TC, LDL-C, and non-HDL-C and incident AF, and a positive association between HDL-C and AF. 41 In the present study, moderate non-HDL-C showed the lowest risk of incident AF. Low HDL-C may contribute to the risk of incident AF via an increase in the prevalence of CAD and heart failure as risk factors of AF.…”
Section: Study Strengths and Limitationssupporting
confidence: 50%
“…A longitudinal study of the results of health examinations in Japan revealed an inverse association between TC, LDL-C, and non-HDL-C and incident AF, and a positive association between HDL-C and AF. 41 In the present study, moderate non-HDL-C showed the lowest risk of incident AF. Low HDL-C may contribute to the risk of incident AF via an increase in the prevalence of CAD and heart failure as risk factors of AF.…”
Section: Study Strengths and Limitationssupporting
confidence: 50%
“…The pathophysiological imbalance between LDL-C, high density lipoprotein-cholesterol (HDL-C), triglycerides and blood glucose levels (BGL) are already present in the IFG state and increases the risk of coronary heart disease and arrhythmia [13,[22][23][24][25]. Impaired fasting glucose is a preclinical stage of diabetes characterized by intermittent or chronic increases in BGL above 5.5 mmol/L and below 7 mmol/L [26].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Moreover, a few longitudinal studies of the association between blood lipids and AF have yielded inconsistent results. [7][8][9] High levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), which are regarded as risk factors for atherosclerotic CV diseases, were unexpectedly found to be inversely associated with the risk of AF in several observational studies. [5][6][7]9 Moreover, lipid ratios such as TC/high-density lipoprotein cholesterol (HDL-C) and LDL-C/HDL-C that are considered useful indices for stratification of patients with CV diseases have been seldom investigated in AF risk estimation.…”
mentioning
confidence: 99%